Specialty Payment Model Opportunities and Assessment: Gastroenterology and Cardiology Model Design Report - Mulcahy, Andrew W. (Rand Health Q, 2015)
Gastroenterology and cardiology services are common and costly among Medicare beneficiaries. Episode-based payment, which aims to create incentives for high-quality, low-cost care, has been identified as a promising alternative payment model. This article describes research related to the design of episode-based payment models for ambulatory gastroenterology and cardiology services for possible testing by the Center for Medicare and Medicaid Innovation at the Centers for Medicare and Medicaid Services (CMS). The authors analyzed Medicare claims data to describe the frequency and characteristics of gastroenterology and cardiology index procedures, the practices that delivered index procedures, and the patients that received index procedures. The results of these analyses can help inform CMS decisions about the definition of episodes in an episode-based payment model; payment adjustments for service setting, multiple procedures, or other factors; and eligibility for the payment model.